Facilities provision in public tertiary education institutions for employability in a competitive society - Florence U. Akudo; Martha-Rose Ifeoma Uwaezuoke (S&Co Publishing, 2024)
The study which investigated facilities provision in public tertiary education for employability in a competitive society in Anambra State was anchored on two research questions and two hypotheses. Descriptive survey research design was employed. The population of the study comprised 6 public tertiary institutions in Anambra State. Total enumeration sampling technique was utilized thus all the 6 government tertiary institutions were used for the study. 50 lecturers and 100 students were selected in each of these public tertiary institutions as respondents numbering 900. The researchers developed an instrument titled “Facilities Provision in Tertiary Education for Employability Questionnaire” (FPTEEQ) which was used to elicit information from the participants. The validity of the instrument was certified, an internal consistency reliability test was conducted and yielded an index of 0.85 thus considered reliable. The administration of the instrument was carried out by the researchers and two trained research assistants, the collected data were coded, weighted and analyzed in accordance with the research questions. Mean and standard deviation was used to answer the research questions while t-test statistics was used to test the hypothesis at 0.05 level of significance. The findings of the study revealed but not limited to: there is acute inadequate provision of relevant mobile educational materials in tertiary education institutions in Anambra State. The researchers therefore recommended that the appropriate agencies should expedite action in the provision of needed educational facilities to ensure credible production of employable graduates that could triumph and excel in the competitive labor market globally.